Role of Pranavaha Srota Dushti in Tamaka Shwasa - Dalabehera, Samikshya; Mohanta, Sarita; Sahu, Manoranjan (International Research Journal of Ayurveda & Yoga, 2024)
In Ayurveda, “Srotas” refers to the channels or pathways within the human body through which substances flow. These channels are responsible for the movement of various elements such as nutrients, waste products, Dosha, and other vital substances. The concept of Srotas is fundamental in Ayurvedic medicine, as the proper functioning of these channels is essential for maintaining health and preventing disease. Pranavaha Srotas essentially means channels carrying the vital life force known as Prana. Dushti, referring to vitiation or dysfunction, thereby describes conditions where these channels are obstructed or malfunctioning, preventing Prana from adequately reaching all areas of the body. The resultant energy blockages can lead to numerous disorders, notably respiratory conditions. Dushti occurs from several factors like environmental toxins, inappropriate diet, or lifestyle habits, manifesting symptoms like breathlessness, diminished body energy levels, coughs, or colds. Tamaka Shwasa, an Ayurvedic correlate for Bronchial Asthma, is characterized by Kapha and Vata imbalance. Ayurvedic texts describe it as a very chronic, recurrent condition marked by symptoms such as wheezing, chest tightness, coughing, and difficulty breathing, with the condition generally worsen during dawn and dusk. The treatment approach typically involves pacifying aggravated Dosha i.e Vata and Kapha, strengthening the patient’s immunity, and adopting dietary and lifestyle modifications. These two conditions, Pranavaha Srotas Dushti and Tamaka Shwasa, are often seen as interconnected in Ayurveda’s understanding of respiratory health. Both signify an imbalance in the body’s energy (Prana) flow due to physical or environmental factors, leading to respiratory conditions. Further exploration and consolidation of Ayurvedic knowledge with modern medicine’s advancements may pave the way for more integrative health-care strategies, providing a comprehensive approach to managing respiratory health.